Training on Making Learning Videos through Bandicam and Droidcam Applications for Teachers Elementary Schools - Aan Widiyono; Muhimmatun Nofiyanti; Harisatul Minnah; Lailatuz Zahro; Lathifatul Inayah; Muhammad Ulil Absor (Institute for Research and Community Services, 2022)
This community service program was initiated in response to the issue of teachers’ lack of skills in conducting online learning using online media. The program was held at SDN 1 Gerdu Pecangaan Jepara, involving eight teachers as participants. Through demonstrations and direct training for each participant, this activity was aimed to improve the teachers’ creativity in teaching with Bandicam and Droidcam applications. It is expected that the teachers can make use of both applications effectively, utilizing laptops or computers and smartphones to further support their students’ learning. The program outcomes showed that the assistance provided in the video productions using the Bandicam application could enhance the quality of the learning process at SDN 1 Gerdu. The teachers’ understanding of the learning applications was observed to improve, with the results of the post-test showing that 75% of the teachers were able to make learning videos using Bandicam and Droidcam applications well. The program has benefitted the teachers in that they can now make learning videos using Bandicam and Droidcam applications to improve their lessons for various materials, which will eventually help their students learn more effectively.